2018
DOI: 10.1101/282053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of whole-genome and NETRIN1 signaling pathway-derived polygenic risk scores for Major Depressive Disorder and thalamic radiation white matter microstructure in UK Biobank

Abstract: Background: Major Depressive Disorder (MDD) is a clinically heterogeneous psychiatric disorder with a polygenic architecture. Genome-wide association studies have identified a number of risk-associated variants across the genome, and growing evidence of NETRIN1 pathway involvement. Stratifying disease risk by genetic variation within the NETRIN1 pathway may provide an important route for identification of disease mechanisms by focusing on a specific process excluding heterogeneous risk-associated variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…There are two potential reasons for the above results. First, deficits in microstructure of the thalamic radiation may be particularly susceptible to the influence by early life factors (43; 44), and second, they may relate to genetic predisposition to depression (17). Although the observational data in the present study did not allow for causal inferences, in future studies, thalamic radiations may be a possibly strong candidate as a causal biomarker for illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two potential reasons for the above results. First, deficits in microstructure of the thalamic radiation may be particularly susceptible to the influence by early life factors (43; 44), and second, they may relate to genetic predisposition to depression (17). Although the observational data in the present study did not allow for causal inferences, in future studies, thalamic radiations may be a possibly strong candidate as a causal biomarker for illness.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, the mean age of participants was 63.06 years (SD = 7.44) and 47.14% were men. We then conducted further data quality control of the remaining participants, removing outliers(16; 17). Finally, the imaging data was merged with other relevant phenotypic data, including measures of depressive symptoms (steps listed below and presented in Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we first investigated the associations between these measures of depressive symptoms and white matter microstructure because of the growing evidence of an association between mood disorders and reductions of white matter microstructure in the limbic system, especially in the thalamic radiations (16,17). These networks contain important tracts involved in emotional processing (18) and regulation (19).…”
Section: See Commentary On Page 734mentioning
confidence: 99%
“…10,11,[13][14][15][16][17][18] In humans, an autosomal-dominant DCC mutation results in structural and functional alterations in the connectivity of mesocortical pathways, with an associated decrease in novelty-seeking behaviour and cigarette use. 19,20 An increasing number of meta-analyses of genome-wide association studies and postmortem human studies have shown that altered levels of DCC expression and the presence of specific genetic polymorphisms in the DCC gene are associated with psychiatric conditions, 21 most notably major depressive disorder, 15,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] schizophrenia 34,[36][37][38] and drug abuse. 19,[39][40][41][42] A study by the Cross-Disorder Group of the Psychiatric Genomics Consortium 3 revealed that a PFC-enriched network of genes prominently affected 8 psychiatric disorders, and a DCC single nucleotide polymorphism (SNP) showed the highest pleiotropic association with all 8 disorders.…”
Section: Introductionmentioning
confidence: 99%